eCM 2018
DOI: 10.22203/ecm.v035a18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human platelet lysate on the expansion and chondrogenic capacity of cultured human chondrocytes for cartilage cell therapy

Abstract: High hopes have been pinned on regenerative medicine strategies in order to prevent the progression of cartilage damage to osteoarthritis, particularly by autologous chondrocyte implantation (ACI). The loss of chondrocyte phenotype during in vitro monolayer expansion, a necessary step to obtain sufficient cell numbers, may be a key limitation in ACI. In this study, it was determined whether a shorter monolayer expansion approach could improve chondrogenic differentiation. The effects of two supplement types, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…With both supplements, the cells appeared flattened and elongated. Pereira et al (2013) and Sykes et al (2018) reported a similar observation. They found that the phenotype of monolayer chondrocytes cultured with HPL changed from polygonal to spindle-shaped.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…With both supplements, the cells appeared flattened and elongated. Pereira et al (2013) and Sykes et al (2018) reported a similar observation. They found that the phenotype of monolayer chondrocytes cultured with HPL changed from polygonal to spindle-shaped.…”
Section: Discussionsupporting
confidence: 66%
“…Cultures supplemented with HPL could yield up to 4-fold more cells. Several researchers have reported the ability of HPL to promote the proliferation of cultured chondrocytes (Hildner et al 2015;Sykes et al 2018). Interestingly, the cell clustering and overlapping in culture did not affect the cell viability, which was >90%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations